Peran Trust dalam Memediasi Pengaruh Digital Marketing dan Literasi Digital terhadap Loyalitas Nasabah pada LPD Desa Adat Panjer - Putu Agus Andika Putra; Luh Putu Mahyuni (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study aims to analyze the effect of digital marketing and digital literacy on customer loyalty and the role of trust in mediating these relationships at the LPD of Desa Adat Panjer. This research employed a quantitative approach with an explanatory research design. The population of this study consisted of all customers of the LPD of Desa Adat Panjer totaling 71 respondents; therefore, a saturated sampling technique was applied. Data were collected through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that digital marketing and digital literacy have a significant effect on customer loyalty. Trust also has a significant effect on customer loyalty. However, trust does not mediate the effect of digital marketing and digital literacy on customer loyalty. These findings indicate that customer loyalty at LPD is not solely determined by trust but is also influenced by other factors such as perceived value and service satisfaction.